Assessment of mechanical properties and environmental benefits of using rice husk ash and marble dust in concrete. (December 2020) - Varadharajan, S.; Jaiswal, Animesh; Verma, Shwetambara
Abstract: The cement is produced on a massive scale in developing countries like India, which leads to the generation of a large amount of carbon dioxide. The cement can be substituted by fillers like rice husk ash (RHA) possessing cementitious property. The use of such fillers results in economy and strength enhancement. This research work aims to replace cement with RHA in percentages varying from 0% to 20%. Also, it is proposed to use marble waste powder (MWP) in the concrete as a substitute for fine aggregate in percentage varying from 0% to 30%. The use of MWP provides huge economic benefits and strength enhancement due to micro filling effect. The hooked steel fibers have been used in a proportion of 1.5% by weight of cement to enhance mechanical and permeability properties. The experimental results showed that optimum combination was obtained for 15% RHA, 30% MWP and 1.5% hooked steel fibres. A maximum enhancement of 44.4%, 60%, and 46.13%, in compressive, tensile, and flexural strength for the optimum combination. In addition, porosity and water absorption reduced with the inclusion of RHA, MWP and steel fibres. The economic feasibility study showed a reasonable enhancement of cost in the inclusion of RHA, MWP & steel fibres, which is justified in return for an excellent improvement in mechanical and permeability properties along with the positive impact on the environment. The experimental results were compiled, and regression analysis was conducted to propose new equations to estimate compressive, splitting tensile, and flexural strength. The proposed equations showed close agreement with experimental results with high correlation coefficients. Furthermore, environmental assessment of the addition of MWP in concrete was evaluated using Recipe midpoint and endpoint analysis. The environmental impact assessment showed that utilization of RHA & MWP adds a valuable contribution and positive impact in minimizing the environmental pollution resulting in a sustainable and clean environment.